Strava-Based training program to increase VO2max capacity of undergraduate students - Aland Jonela; Bafirman Bafirman; Umar Umar; Wilda Welis (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to develop and evaluate the effectiveness of a Strava-based endurance training program in improving VO₂max among undergraduate students of the Sports Science Study Program, Universitas Negeri Padang. The research applied a Research and Development (R&D) approach using selected stages of the ADDIE model, combined with a one-group pretest–posttest design. Sixteen students (aged 21–24 years) participated in a 5-week training program conducted 3–4 sessions per week, consisting of continuous running and tempo running at moderate to high intensity. VO₂max was measured using a 2.4 km run test with a validated estimation formula. Results showed an increase in mean VO₂max from 35.10 ml/kg/min (pretest) to 42.18 ml/kg/min (posttest), indicating an improvement of 7.08 ml/kg/min (≈20.2%). A paired sample t-test revealed a significant difference (p < 0.05). These findings suggest that the Strava-based training program is effective, although further studies with control groups and larger samples are recommended.